Perceived stress level and health anxiety during COVID-19 pandemic period in patients with diabetes mellitus and hypertension: A prospective cross-sectional study - Bozkurt, Erhan; Kurtses Gürsoy, Betül; Atay, Emre; Bilir, Abdülkadir; Kaynarca, Önder (Journal of Surgery and Medicine, 2021)
Background/Aim: Mortality rates of Coronavirus Disease 2019 (COVID-19) are increased in patients with chronic diseases such as diabetes mellitus (DM) and hypertension (HT). For this reason, some restrictions and lockdown measures were brought to these patients during the pandemic period, which may have disrupted their mental wellbeing. We aimed to investigate the relationship between the changes in the frequency of admissions of patients with DM, HT, DM+HT to the hospital during the pandemic and their perceived stress, health anxiety, general anxiety, and depression levels, and the change in stress burden experienced by disease type. This study intends to reveal the psychological problems that may develop due to the COVID-19 pandemic in DM, HT, and DM+HT patients and raise awareness. Methods: DM, HT, and DM+HT patients admitted to Internal Medicine Outpatient Clinic between 01.12.2020-01.02.2021, and healthy volunteers who accepted to participate were included in this prospective cross-sectional study. Patients who did not match the age range, had additional comorbidities besides DM and HT, were treated for psychiatric disease, or were pregnant, and those who did not give consent were excluded. After a psychiatric interview was performed, the participants were asked to fill in the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Perceived Stress Scale (PSS), and Health Anxiety Scale (HAS). The effects of the COVID-19 pandemic on the frequency of admissions and perceived stress, health anxiety, general anxiety, and depression levels, and the change in stress burden experienced by disease type were examined. Results: There was a significant difference in all scales used between the patient groups and the healthy control group (HAS P<0.001, BDI P<0.001, BAI P=0.002, PSS P=0.001). There was a significant decrease in the frequency of admission to the outpatient clinics among DM + HT patients (P=0.002). The mean duration of disease was lower in individuals whose frequency of admission to the outpatient clinic decreased (P=0.006). Patients with a family history of COVID-19 had significant decreases in the frequency of admission to the outpatient clinic (P<0.001) and had significantly disrupted medical treatment (P=0.007). Conclusion: Patients with DM and HT, a short duration of chronic diseases, and history of COVID-19 infection in their families are more prone to be affected psychologically, and patients who are more psychologically affected refer less to the outpatient clinic. It is essential to continue treatment in consultation with psychiatry if DM and HT patients presenting to the outpatient clinic have one or more of these risk factors.